2020
DOI: 10.1101/2020.07.30.229989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MacaquePose: A novel ‘in the wild’ macaque monkey pose dataset for markerless motion capture

Abstract: Video-based markerless motion capture permits quantification of an animal’s pose and motion, with a high spatiotemporal resolution in a naturalistic context, and is a powerful tool for analyzing the relationship between the animal’s behaviors and its brain functions. Macaque monkeys are excellent non-human primate models, especially for studying neuroscience. Due to the lack of a dataset allowing training of a deep neural network for the macaque’s markerless motion capture in the naturalistic context, it has b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…One of the latest contributions to this toolbox is the opensource software DeepLabCut (DLC) 16 , which uses convolutional neural networks to automatically capture movements and postures directly from images and without requiring active or passive markers. DLC is a modified version of a state-of-the-art algorithm for tracking human movement, DeeperCut 17 and can be used in a broad range of study systems with near human-level accuracy 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the latest contributions to this toolbox is the opensource software DeepLabCut (DLC) 16 , which uses convolutional neural networks to automatically capture movements and postures directly from images and without requiring active or passive markers. DLC is a modified version of a state-of-the-art algorithm for tracking human movement, DeeperCut 17 and can be used in a broad range of study systems with near human-level accuracy 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the generalizability of our dataset, we conduct a cross-dataset evaluation with OpenMonkeyPose (6) and MacaquePose (11). OpenMonkeyPose (6) consists of 195,228 annotated images simultaneously captured by 62 precisely arranged high-resolution video cameras.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Data innovation: the tracking models learn the visual representation from a large annotated dataset that specifies the locations of landmarks. Existing publicly available datasets including OpenMonkeyPose (200K multiview macaque images in a specialized laboratory environment) (6) and Macaque-Pose (13K in-the-wild macaque images) (11) are important resources for the development of tracking algorithms, and as such, extend the boundary of pose tracking performance of NHPs. However, due to limited data diversity (appearance, pose, viewpoint, environment, and species), existing datasets are currently insufficient for learning generalizable tracking models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a deep learning approach is feasible [5][6] [7]. Although monkey pose could be estimated accurately, these works are limited to a single subject.…”
Section: Related Workmentioning
confidence: 99%